DESAIN EKSPERIMEN TAGUCHI UNTUK MENINGKATKAN KUALITAS PUPUK ORGANIK BERBAHAN BAKU KOTORAN KELINCI - Nasir Widha Setyanto; Lely Riawati; Rio Prasetyo Lukodono (Badan Penerbit Jurnal, Faculty of Engineering, Universitas Brawijaya, 2014)
Currently one of the organic fertilizer started being used is organic fertilizer from rabbit feces. In Pesanggrahan Batu area, there are about 25 farmers in each farmer has about 50 rabbits and joinning to